Comparative evaluation of the energy and economic efficiency of vapor compression heat pumps in modernization of large chemical and oil refining industries. Part 2 - V. L. Yusha; M. A. Sutyaginskiy; Yu. A. Potapov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The question of the expediency of increasing the energy efficiency of a large chemical and oil refining industry by using process heat carriers and raw materials as heaters of vapor compression heat pumps based on systems for recuperating heat process losses is considered. A feature of the energy system under consideration is the provision of the main circuit of the heat pump and its drive from a common source of thermal energy. The influence of the temperature parameters of the consumer of highpotential thermal energy, the source of low-potential thermal energy and the energy efficiency of the main functional elements of the energy system under consideration on the ratio of the amount of generated thermal energy supplied to the consumer to the amount of thermal energy losses used is analyzed. In addition, an assessment is made of the influence of the listed factors on the redistribution of low-potential thermal energy flows between the main circuit of the heat pump and its drive. The presented results reflect the fundamental possibility of increasing the temperature level of process heat carriers and raw materials without significant costs for additional external energy sources. The efficiency of reuse of heat losses in a closed technological cycle depends on the temperature conditions of the consumer and the source of thermal energy in the heat pump cycle, on the connection scheme of the thermal energy source and on the energy efficiency of the equipment used.